2015
DOI: 10.1007/s11418-015-0925-5
|View full text |Cite
|
Sign up to set email alerts
|

A bibenzyl from Dendrobium ellipsophyllum inhibits migration in lung cancer cells

Abstract: Metastatic cancer cells have been shown to have aggressive behaviors accounting for the high incidence of chemotherapeutic failure and mortality. Because migration and invasion are crucial behaviors for cancer cell dissemination, promising compounds exhibiting potential antimigration effects are of interest for metastasis-based therapeutic approaches. This study aimed to evaluate the activity of a bibenzyl, 4,5,4'-trihydroxy-3,3'-dimethoxybibenzyl (TDB), isolated from Dendrobium ellipsophyllum Tang and Wang, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…Our results demonstrate that the PNEE increases E-cadherin expression to maintain the integrity of cell-cell stroma. Previous studies have also shown that ethanol-soluble extracts of Cochinchina momordica seeds, an anticancer ingredient in China, and bibenzyl, an active component of Dendrobium ellipsophyllum, can inhibit the epithelial-to-mesenchymal transition (EMT) by increasing the level of E-cadherin in human lung cancer A549 and H292 cells, respectively, resulting in the inhibition of human lung cancer cell migration and invasion (Chaotham et al, 2014;Shen et al, 2015). The suppressive effect of the PNEE on migration and invasion may be an important factor that contributes to the observed antimigration effect.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that the PNEE increases E-cadherin expression to maintain the integrity of cell-cell stroma. Previous studies have also shown that ethanol-soluble extracts of Cochinchina momordica seeds, an anticancer ingredient in China, and bibenzyl, an active component of Dendrobium ellipsophyllum, can inhibit the epithelial-to-mesenchymal transition (EMT) by increasing the level of E-cadherin in human lung cancer A549 and H292 cells, respectively, resulting in the inhibition of human lung cancer cell migration and invasion (Chaotham et al, 2014;Shen et al, 2015). The suppressive effect of the PNEE on migration and invasion may be an important factor that contributes to the observed antimigration effect.…”
Section: Discussionmentioning
confidence: 99%
“…Geraniin has been shown to inhibit TGF-β1-induced EMT of lung cancer A549 cells in vitro by inducing the epithelial marker E-cadherin and suppressing Snail and mesenchymal marker N-cadherin and vimentin [26]. A compound derived from Dendrobium ellipsophyllum, bibenzyl 4,5,4′ -trihydroxy-3,3′-dimethoxybibenzyl was shown to inhibit EMT of lung cancer cells via downregulating EMT markers (vimentin and Snail) and upregulating E-cadherin [27]. Such EMT suppression was also observed in lung cancer cells treated with other single compounds obtained from Chinese medicine, such as moscatilin [28], gigantol [29], and epicatechin-3-gallate [30].…”
Section: Suppression Of Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…Several natural products have been shown to have abilities to suppress EMT in lung cancer cells. A bibenzyl 4,5,4'-trihydroxy-3,3'-dimethoxybibenzyl [TDB,7], isolated from Dendrobium ellipsophyllum, has been demonstrated to inhibit EMT and sensitize lung cancer cells to anoikis (57). Treatment of lung cancer cells with non-toxic concentrations of TDB significantly suppressed EMT markers, namely vimentin and Snail, while increased the level of E-cadherin.…”
Section: Cancer Metastatic Process Metastasis Is a Complicated Multimentioning
confidence: 99%
“…Treatment of lung cancer cells with non-toxic concentrations of TDB significantly suppressed EMT markers, namely vimentin and Snail, while increased the level of E-cadherin. Also, such a decrease in EMT phenotypes was shown to induce anoikis and decrease cell growth in detached conditions by reduction of activated protein kinase B (p-AKT) and activated extracellular signalregulated kinase (p-ERK) (57). Gigantol [8], extracted from Dendrobium draconis, and known bibenzyl compounds, including moscatilin [9], chrysotobibenzyl [10], chrysotoxine [11] and crepidatin [12], isolated from Dendrobium pulchellum, have been demonstrated to suppress EMT in a lung cancer cell model and such suppression resulted in the induction of anoikis and decreased growth in an anchorage-independent manner (58,59).…”
Section: Cancer Metastatic Process Metastasis Is a Complicated Multimentioning
confidence: 99%